2009
DOI: 10.1016/j.vetmic.2009.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Swine torque teno virus (TTV) infection and excretion dynamics in conventional pig farms

Abstract: 14Torque teno virus (TTV) is a non-enveloped, single stranded DNA (ssDNA) 15 virus infecting human and non-primate species. Two genogroups of TTV (TTV1 and 16 TTV2) have been described in swine so far. In the present study, TTV1 and TTV2 17 prevalences in serum, and nasal as well as rectal swabs of 55 randomly selected piglets 18 from seven Spanish multi-site farms, were monitored from 1 to 15 weeks of age. Also, 19 blood from their dams (n=41) were taken at 1 week post-farrowing. Samples were 20 tested by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 29 publications
8
35
2
Order By: Relevance
“…These results indicate that TTSuV infection has spread to pigs of all production stages. Finisher pigs had significantly higher rates of TTSuV detection than animals from the other stages, in agreement with previous studies that have reported that TTSuV infection increases with the age of the animals (Sibila et al 2009b, Aramouni et al 2010). …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results indicate that TTSuV infection has spread to pigs of all production stages. Finisher pigs had significantly higher rates of TTSuV detection than animals from the other stages, in agreement with previous studies that have reported that TTSuV infection increases with the age of the animals (Sibila et al 2009b, Aramouni et al 2010). …”
Section: Discussionsupporting
confidence: 92%
“…In our study, the overall percentage of TTSuV-positive pigs (66.3%) was higher than that described in a study performed with rectal swabs (Sibila et al 2009b), which reported a low percentage (<20%) of TTSuV detection. Previous studies reported higher rates for TTSuV in fecal samples, suggesting that the fecal-oral route is an important route of TTSuV transmission (Brassard et al 2008, Leme et al 2012).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations